The role of living donor liver transplantation in treating intrahepatic cholangiocarcinoma - Andraus, Wellington; Ochoa, Gabriela; de Martino, Rodrigo Bronze; Pinheiro, Rafael Soares Nunes; Santos, Vinicius Rocha; Lopes, Liliana Ducatti; Arantes Júnior, Rubens Macedo; Waisberg, Daniel Reis; Santana, Alexandre Chagas; Tustumi, Francisco; D’Albuquerque, Luiz Augusto Carneiro (Frontiers in Oncology, 2024)
Introduction: Intrahepatic cholangiocarcinoma (iCC) is the liver's second most common neoplasm. Until now, surgery is the only curative option, but only 35% of the cases are considered resectable at the diagnosis, with a post-resection survival of around 30%. Advancements in surgical techniques and perioperative care related to liver transplantation (LT) have facilitated the expansion of indications for hepatic neoplasms. Method: This study is a comprehensive review of the global experience in living donor LT (LDLT) for treating iCC and describes our first case of LDLT for an unresectable iCC. Results: While exploring LT for intrahepatic cholangiocarcinoma dates to the 1990s, the initial outcomes were discouraging, marked by poor survival and high recurrence rates. Nevertheless, contemporary perspectives underscore a reinvigorated emphasis on extending the frontiers of LT indications within the context of the "oncologic era." The insights gleaned from examining explants, wherein incidental iCC was categorized as hepatocellular carcinoma in the preoperative period, have demonstrated comparable survival rates to small hepatocellular carcinoma. These findings substantiate the potential viability of LT as a curative alternative for iCC. Another investigated scenario pertains to "unresectable tumors with favorable biological behavior," LT presents a theoretical advantage by providing free margins without the concern of a small future liver remnant. The constraint of organ shortage persists, particularly in nations with low donation rates. LDLT emerges as a viable and secure alternative for treating iCC.LDLT is an excellent option for augmenting the graft pool, particularly in carefully selected patients.